Coexistence of blaNDM-1 and blaIMP-4 in One Novel Hybrid Plasmid Confers Transferable Carbapenem Resistance in an ST20-K28 Klebsiella pneumoniae - Jia, Xinmiao; Jia, Peiyao; Zhu, Ying; Yu, Wei; Li, Xue; Xi, Jingyuan; Liu, Xiaoyu; Liao, Kang; Xu, Yingchun; Cheng, Bin; Yang, Qiwen (Frontiers in Microbiology, 2022)
Objectives: We identified a novel hybrid plasmid simultaneously carrying blaNDM-1 and blaIMP-4 in an ST20-K28 carbapenem-resistant Klebsiella pneumoniae (CRKP) strain AZS099 and reported its detailed genetic and phenotypic characterization. Methods: Antimicrobial susceptibility was characterized using broth microdilution method. Complete genome characteristics and plasmid detailed analysis were carried out by PacBio Sequel and Illumina sequencing and further bioinformatics analysis. Conjugation assay, S1-PFGE, Southern blot, plasmid stability, and fitness cost were conducted to the phenotypic characterization of this novel hybrid plasmid. Results: AZS099 was isolated from a blood specimen obtained from a 3-month baby who presented with biliary tract infection. Susceptibility testing showed that AZS099 was resistant to almost all β-lactams examined, including cephalosporins, combinations of β-lactams and β-lactamase inhibitors, carbapenems, and aztreonam. PacBio and Illumina sequencing together with S1-PFGE and Southern blot showed that blaNDM-1 and blaIMP-4 were simultaneously located on a 296 kb IncFIB(K)/IncHI1B/IncX3 plasmid (pAZS099-NDM-IMP), which is consists of four main parts that came from four different types of plasmids. The region harboring blaIMP-4 is located in a class 1 integron designated as In0, which is located in an IS6100-IS26 transposon-like structure with a total length of ~5 kb. The region harboring blaNDM-1 is located in the Tn125 transposon remnant. Conjugation and transformation assay confirmed that the plasmid pAZS099-NDM-IMP has the potential for horizontal transfer and displayed high stability (retention rate >95%). Furthermore, growth curve assessment confirmed that the presence of pAZS099-NDM-IMP exhibit no growth pressure on bacteria. Conclusion: Our research reported a hybrid plasmid coharboring blaNDM-1 and blaIMP-4 in an ST20-K28 CRKP strain. The emergence of novel hybrid plasmid could threaten the control of antimicrobial resistance and should be closely supervised.